Strengthening Adaptive Capacity of Extensive Livestock Systems for Food and Nutrition Security and Low-emissions Development in Eastern and Southern Africa - Dekesa, Chipo; Mubaya, Chipo P; Makonnen, Brook T. (International Livestock Research Institute, 2024)
This report provides an overview of the virtual training sessions on gender and social analysis held on April 25, 2024. The sessions were facilitated by Professor Chipo Mubaya and Mrs. Chipo Dekesa, a PhD fellow from the Chinhoyi University of Technology, who are part of the ACIAR-funded project entitled, ‘Strengthening the adaptive capacity of extensive livestock systems for food and nutrition security and low-emissions development in Eastern and Southern Africa.’ The report briefly summarizes the project and training, providing context regarding gender and social analysis in extensive livestock systems. The report also highlights the key points that emerged from the interactive training sessions and key questions and responses from the participants.